Pagan Terror: The Role of Pagan Ideology in Church Burnings and the 1990s Norwegian Black Metal Subculture - Vrzal, Miroslav (Pomegranate, 2018)
The church burnings wave of the early 1990s in Norway, connected with the emerging black metal subculture of the time, is often associated with Satanism, and the burnings are sometimes labeled as “Satanic terrorism.” Instead, the text argues that some arsons may be rather seen as Pagan terrorism, since some of the leading figures in the early Norwegian black metal subculture (especially Varg Vikernes) have indicated that their acts were inspired by their own personal versions of Paganism. These church-burners have described themselves as the successors of the Vikings of old and as “Pagan warriors” continuing an age-long war against Christianity and its culture. Using Mark Juergensmeyer’s terms we can understand such actions against Christianity as a type of cosmic war, employing public performances with high shock value.